Nuclear magnetic resonance analysis of water in natural and deuterated mouse muscle above and below freezing. - Peemoeller, H (1980)
Measurements of absolute proton signal intensities, free induction decays, spin-spin relaxation times, and local fields in the rotating frame in natural and fully deuterated mouse muscle at five temperatures in the range 293-170 K are reported. The analysis is carried out at three time windows on the free induction decay. The contribution to the magnetization from protons on large molecules and water are analyzed.